Implementation of M-Passport Application in Improving the Quality of Public Services : JEL Classification: K11, K12, K24, O34, D18 - Rafi, Fadliastuti; Hamid, Muliyadi; Arif, Muhammad Ridwan (Journal La Bisecoman, 2025)
This study aims to (1) provide an overview of the implementation of the M-Passport application in the Passport service process, (2) assess its effectiveness and efficiency in improving service processes, and (3) identify obstacles faced during its implementation at the Makassar Class I TPI Immigration Office. The research adopts a mixed-method approach, involving 42 passport applicants and managers. Data were collected through interviews, questionnaires, and observations, and analyzed using data triangulation. The M-Passport application has significantly improved service procedures, offering clear, accessible guidelines for applicants. It ensures timely service completion and transparent payment details, enhancing overall user satisfaction. The application is supported by adequate infrastructure, including waiting areas, playrooms, breastfeeding rooms, separate toilets for public use and disabilities, and dedicated counters for Indonesian and foreign applicants. Information and service ambassadors are also available to assist users. The effectiveness of Passport services using the M-Passport application is rated at 84.56% ("Good"), while efficiency is rated at 83.88% ("Good"). Despite these achievements, challenges remain. Frequent maintenance and updates can render the application inaccessible for 2–3 days. Network issues also affect accessibility, while limited-service quotas occasionally prevent applicants from securing preferred schedules. the M-Passport application has improved the service experience at the Makassar Immigration Office but requires addressing maintenance, network reliability, and quota limitations to enhance its effectiveness and efficiency further.